Prevalence of common mental disorders among sugarcane workers - Polyana Felipe Ferreira da Costa; Solange Laurentino dos Santos; Marcelo Saturnino da Silva; Idê Gomes Dantas Gurgel (Universidade de São Paulo, 2017)
ABSTRACT OBJECTIVE To estimate the prevalence of common mental disorders and to analyze the associated factors in migrant and sugarcane workers. METHODS This is a cross-sectional study carried out with 110 workers. Common mental disorders were evaluated using the Self-Reporting Questionnaire (SRQ-20), and sociodemographic, occupational, and lifestyle variables were studied. The CAGE questionnaire was used to detect the abuse of alcoholic beverages. RESULTS The prevalence of common mental disorders affected 40% of the workers and the association showed statistical significance for the positive result of the CAGE test, sickness, absence from work, and medical care during the harvest period. CONCLUSIONS The suspected cases of problem drinkers and the control mechanisms used by the mill for workers who miss work or become ill are factors that can cause common mental disorders.